The Geographic Flow of Bank Funding and Access to Credit: Branch Networks, Synergies, and Local Competition - Aguirregabiria, Victor; Clark, Robert; Wang, Hui (American Economic Review, 2025)
Geographic dispersion of depositors, borrowers, and banks may prevent funding from flowing to high-loan-demand areas, limiting credit access. Using bank-county-year-level data, we provide evidence of geographic imbalance of deposits and loans and develop a methodology for investigating the contribution to this imbalance of branch networks, market power, and scope economies. Results are based on a novel measure of imbalance and estimation of a structural model of bank competition that admits interconnections across locations and between deposit and loan markets. Counterfactual experiments show branch networks, scope economies, and local competition affect credit flow to disadvantaged markets. (JEL C43, G21, G28, L13, R32)